Implementation and performance evaluation of an intelligent fuzzy-based testbed for WSANs: a case study for object tracking. (2018) - Elmazi, Donald; Ikeda, Makoto; Barolli, Leonard
Wireless sensor and actor networks (WSANs) have emerged as a variation of wireless sensor networks. WSANs are capable of monitoring physical phenomenons, processing sensed data, making decisions based on the sensed data and completing appropriate tasks when needed. In this paper, we propose an intelligent fuzzy-based testbed that based on data provided by sensors and actors selects an appropriate actor node. From the evaluation results, the system selects the actors in order to have low latency and proper task assignment considering multi actors for different job types.